Pop Art - Osterwold, Tilman (Köln : Benedikt Taschen Verlag GmbH, 1992)
Arman ; Artschwager, Richard ; Barker, Clive ; Bengston, Billy Al ; Blake, Peter ; Boshier, Derek ; Caulfield, Patrick ; Christo ; D'Arcangelo, Allan ; Dine, Jim ; Errò ; Fahlström, Öyvind ; Goode, Joe ; Grooms, Red ; Hains, Raymond ; Hamilton, Richard ; Hockney, David ; Indiana, Robert ; Johns, Jasper ; Johnson, Ray ; Jones, Allen ; Kanovitz, Howard ; Kienholz, Edward ; Kitaj, R.B. ; Lichtenstein, Roy ; Lindner, Richard ; Marisol ; Oldenburg, Claes ; Paolozzi, Eduardo ; Phillips, Peter ; Ramos, Mel ; Rauschenberg, Robert ; Richter, Gerhard ; Rivers, Larry ; Rosenquist, James ; Ruscha, Edward ; Segal, George ; Smith, Richard ; Thiebaud, Wayne ; Tilson, Joe ; Vostell, Wolf ; Warhol, Andy ; Wesselmann, Tom ; Westermann, Horace Clifford
Nederlands
boek
Keywords: Europa; Groot-Brittannië; Amerika